2022
DOI: 10.3390/biom12081046
|View full text |Cite
|
Sign up to set email alerts
|

PGRMC1 Regulates Cellular Senescence via Modulating FOXO1 Expression in Decidualizing Endometrial Stromal Cells

Abstract: The appropriate differentiation of endometrial stromal cells (ESCs) into decidual cells is required for embryo implantation and subsequent placentation into humans. Decidualization is accompanied by the appearance of senescent-like cells. We recently reported the secretory phase-specific downregulation of endometrial progesterone receptor membrane component 1 (PGRMC1) and enhanced decidualization upon PGRMC1 knockdown and inhibition in cultured ESCs. However, it remains unknown whether PGRMC1 is involved in ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Downregulating PGRMC1 after progestin treatment doesn't hamper decidualization, indicating its critical role during the increasing phase and induction. This aligns with observations that PGRMC1 downregulation in the secretory phase promotes decidualization [34]. Overall, PGRMC1 activation by P4 may facilitate the switch from cellular proliferation to decidualization initiation through various biological processes, while the mechanism of how downregulated PGRMC1 promotes decidualization warrants further investigation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Downregulating PGRMC1 after progestin treatment doesn't hamper decidualization, indicating its critical role during the increasing phase and induction. This aligns with observations that PGRMC1 downregulation in the secretory phase promotes decidualization [34]. Overall, PGRMC1 activation by P4 may facilitate the switch from cellular proliferation to decidualization initiation through various biological processes, while the mechanism of how downregulated PGRMC1 promotes decidualization warrants further investigation.…”
Section: Discussionsupporting
confidence: 87%
“…AG205 was reported to be a speci c inhibitor of PGRMC1 and was broadly used to explore PGRMC1's role in decidualization [34,35]. Recent data, however, question the speci city of AG205 for PGRMC1 [35][36][37].…”
Section: The Interactions Between Pgrmc1 and Phb1 (mentioning
confidence: 99%
“…Second, interleukin 15 (IL-15) recruits and activates uNK cells at the maternal–fetal interface. The uNK cells remove senescent decidual cells through granule exocytosis, and the interactions between senescent and immune cells ensure embryo invasion and anchoring to the endometrium [47, 48].…”
Section: Physiological Cell Senescence At the Maternal–fetal Interfacementioning
confidence: 99%
“…Essentially, cell senescence contributes to the transition of the cycling endometrium into the receptive pregnant decidua [46]. During implantation, EnSCs release SASP factors to create a transient inflammatory environment, which not only contributes to the reprogramming of clonal mesenchymal stem-like cells and induces secondary senescent cells but also recruits uNK cells to limit the process [47]. Altogether, these studies have demonstrated the cooperation between the immune system and senescence at the maternal–fetal interface.…”
Section: Physiological Cell Senescence At the Maternal–fetal Interfacementioning
confidence: 99%
“…Clarke et al [445] showed that conditional ablation of pgrmc1 from female reproductive tissues promoted premature reproductive senescence, which arguably could be associated with accelerated aging of those tissues. In a recent study [446], PGRMC1 attenuation in endometrial stromal cells led to the increased expression of the transcription factor forkhead box protein O1 (FOXO1), and the appearance of senescence associated markers which could be reversed by attenuation of FOXO1 levels. Since senescence is an attribute of aging, and PGRMC1 is strongly implicated in senescent biology, these observations promote a strong argument that PGRMC1 is directly involved in aging biology.…”
Section: Pgrmc1 Is Involved In Metabolic Alterations Associated With ...mentioning
confidence: 99%